POTENSI BIODIVERSITAS INDONESIA SEBAGAI INHIBITOR XANTINA OKSIDASE DAN ANTIGOUT - Yulian, Muammar (Lantanida Journal, 2014)
Tendency for people to go back to nature and the government's policy to "Saintifikasi Jamu" prioritizing in degenerative diseases such as hyperglycemia, hypertension, hypercholesterolemia and hyperuricemia / gout is a condition that is highly prospective and has pushed for the development of research on medicinal plants-based biodiversity Indonesiasebagai state megabiodiversity. Results of research have shown that among the diversity of Indonesia's biodiversity as a potential inhibitor of xanthine oxidase (XO) and antigot is sidaguri (Sida rhombifolia L), celery (Apium graveolens L), fruits (Salacca R. edulis) varieties of Bangkok, ear- earrings (Acalypha indicaL.), and Bitter (Andrographis paniculata, Ness.). Ethanol extract of the herb sidaguri XO inhibitor has potential as indicated by the ability to dampen the activity of XO with IC50 values